2022
DOI: 10.1111/jch.14423
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure in youth in pediatric weight management programs in the Pediatric Obesity Weight Evaluation Registry (POWER)

Abstract: Blood pressure (BP) assessment and management are important aspects of care for youth with obesity. This study evaluates data of youth with obesity seeking care at 35 pediatric weight management (PWM) programs enrolled in the Pediatric Obesity Weight Evaluation Registry (POWER). Data obtained at a first clinical visit for youth aged 3-17 years were evaluated to: (1) assess prevalence of BP above the normal range (high BP); and (2) identify characteristics associated with having high BP status.Weight status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been shown that male sex, older age, and higher BMI z‐score are predictors of cIMT, an established marker of atherosclerosis 27 . In the recent “POWER” study in youth with obesity/overweight, having high BP was positively associated with severe obesity, older age (15 to 17 years), and male sex 33 . However, the role of gender in the accumulation of CVRFs in children and adolescents with diabetes and hypertension and its relationship with target organ damage and future CVD requires further investigation in long‐term follow‐up studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that male sex, older age, and higher BMI z‐score are predictors of cIMT, an established marker of atherosclerosis 27 . In the recent “POWER” study in youth with obesity/overweight, having high BP was positively associated with severe obesity, older age (15 to 17 years), and male sex 33 . However, the role of gender in the accumulation of CVRFs in children and adolescents with diabetes and hypertension and its relationship with target organ damage and future CVD requires further investigation in long‐term follow‐up studies.…”
Section: Discussionmentioning
confidence: 99%